PREFERENSI, POLA KONSUMSI, DAN KEPUASAN KONSUMEN GULA SEMUT DI PASAR MODERN KOTA BANDAR LAMPUNG - Salsabila, Luthfia Nur; Prasmatiwi, Fembriarti Erry; Suryani, Ani (Lampung University, 2025)
This research aims to analyze preferences, consumption patterns, and consumer satisfaction for crystal palmsugar at modern markets in Bandar Lampung City. The research method used was the survey method. Datawas collected in February 2025 with a total number of respondentwere 60 people taken by the accidentalsampling method at four different modern market , namely Chandra Supermarket, Chandra Mini Market,Super Indo, and Fitrinofane. The analysis used was conjoin analysis, quantitative descriptive, CustomerSatisfaction Index (CSI), and Importance Performance Analysis (IPA). The results reveal that consumerpreferences for crystal palm sugar at modern markets in Bandar Lampung City are fragrant aroma, coarsegrain texture, dark brown color, and standing pouch packaging with size of 250 gram. The consumption ofcrystal palm sugar is as an alternative sweetener, and the brands that are widely purchased are Aromanis,Haan, and Edna. Consumer usually buy the palm sugar in the size of 250 gram with a frequency ofpurchase is once to two times, and the total consumption is fifteen times in a month. The amount ofpurchases made is 272 grams in a month, and the amount of consumption is 176 grams in a month. Basedon the analysis, the consumer satisfaction falls into e very satisfied category. Keywords: crystal palm sugar, consumption pattern, consumer satisfaction, preference